To multiply the polynomial expressions \((b + 8)(3b - 6)\), we can use the distributive property (also known as the FOIL method for binomials).
Here’s how you do it step-by-step:
-
First: Multiply the first terms: \[ b \cdot 3b = 3b^2 \]
-
Outer: Multiply the outer terms: \[ b \cdot (-6) = -6b \]
-
Inner: Multiply the inner terms: \[ 8 \cdot 3b = 24b \]
-
Last: Multiply the last terms: \[ 8 \cdot (-6) = -48 \]
Now, combine all these results: \[ 3b^2 - 6b + 24b - 48 \]
Next, combine the like terms: \[ 3b^2 + (24b - 6b) - 48 = 3b^2 + 18b - 48 \]
Therefore, the product of the polynomial expression \((b + 8)(3b - 6)\) is: \[ \boxed{3b^2 + 18b - 48} \]